Atributos do solo e flora infestante em sistema de semeadura direta do milho na palha de leguminosas arbóreas - Macêdo, Jeane Rodrigues de Abreu [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The objective of this study was to evaluate the effect of different combinations of legumes tree in alleys cropping systems with four years on the chemical and physical properties of the soil, and the diversity and dynamics of weed population. The experiment consisted of five treatments with eight replications in a randomized block experimental design: Leucaena leucocephala + Clitoria fairchildiana, L. leucocephala + Acacia mangium, Gliricídia sepium + C. fairchildiana, G. sepium + A. mangium and control (without legumes). The following soil properties were evaluated: organic matter, pH in CaCl2, P, K, Ca, Mg, H + Al, Na, Al, density, porosity and stability of aggregates and calculated the sum of bases (SB), the cation exchange capacity (CEC) and base saturation (V%). The weeds were evaluated for: family, species, number of individuals and biomass and estimated abundance, frequency, dominance and the Importance Value Index (IVI). The floristic diversity was analyzed using the diversity index of Shannon-Wiener (H '). At depth 0-10 cm all treatments affected magnesium concentration. For density and porosity of the soil there were no significant differences between treatments. For the aggregate stability, the values for mean weight diameter (MWD) varied between treatments in the 10-20 cm layer, the combinations L. leucocephala + A. mangium and G. sepium + A. mangium presented the highest values. Thirty two plant species belonging to sixteen families were identified. The most representative families were Poaceae, with six species, followed by Cyperaceae and Malvaceae, with four species. The specie Cyperus lanceolatus presented the highest IVI. Leucaena leucocephala + Clitoria fairchildiana and Gliricidia sepium + Acacia mangium presented greater diversity. Regarding the biomass of weeds, there were differences between treatments with the highest value observed for the control treatment. There were no significant differences between ...

Objetivou-se com esse estudo avaliar o efeito de diferentes combinações de leguminosas arbóreas em sistema de cultivo em aleias, com quatro anos, sobre os atributos químicos e físicos do solo e a diversidade e dinâmica populacional de plantas infestantes. O experimento foi constituído por cinco tratamentos com oito repetições em delineamento experimental em blocos casualisados: Leucaena leucocephala + Clitoria fairchildiana; Leucaena leucocephala + Acacia mangium; Gliricidia sepium + Clitoria fairchildiana; Gliricidia sepium + Acacia mangium e o controle (sem leguminosas). Foram avaliados no solo: matéria orgânica, pH em CaCl2, P, K, Ca, Mg, H + Al, Na, Al, densidade, porosidade e estabilidade dos agregados e calculadas a soma de bases (SB), a capacidade de troca catiônica (CTC) e a saturação por bases (V%), As plantas invasoras foram avaliadas quanto a: família, espécie, número de indivíduos e fitomassa, sendo estimados a abundância, a frequência, a dominância e o Índice de Valor de Importância (IVI). A avaliação da diversidade florística foi realizada através do Índice de diversidade de Shannon-Wiener (H'). Na camada de 0 - 10 cm todos os tratamentos afetaram a concentração de magnésio. Para a densidade e a porosidade do solo, não houve diferenças significativas entre os tratamentos. Quanto à estabilidade de agregados, os valores para diâmetro médio ponderado (DMP) variaram estatisticamente entre os tratamentos na camada de 10-20 cm, as combinações L. leucocephala + A. mangium e G. sepium + A. mangium obtiveram os maiores valores. Foram identificadas 32 espécies de plantas, pertencentes a 16 famílias. As famílias mais representativas foram Poaceae, com seis espécies, seguida por Cyperaceae e Malvaceae, com quatro espécies cada. A espécie Cyperus lanceolatus apresentou o maior IVI. Leucena + sombreiro e gliricídia + acácia apresentaram maior diversidade. Em relação à fitomassa das plantas ...
Keywords: Milho; Adubação verde; Plantio direto; Erva daninha; Físico-química do solo; Comunidades vegetais; Soil physical chemistry